Fiscal cost and welfare effects of the maize subsidy - Lustig, Nora (International Food Policy Research Institute, 1988)
The Mexican government has been involved in regulating the prices of staples since the 1930s.1 Formally, the dual objectives of this long-standing intervention have been to protect the rural campesinos (peasants) against speculators and drastic decreases in agricultural prices and to protect poor urban consumers against rising prices in food products. The government uses three methods to pursue these goals. First, it purchases basic grains at guaranteed (support) prices and subsidizes agricultural inputs. Second, it maintains price controls on staples and subsidizes industries that produce them. And, third, it participates directly in the production and marketing of basic foodstuffs.